Red Mud Catalyzed Synthesis of Benzimidazole, Benzothiazoles and Quinoxalines - G. C. Wadhawa , Nitin A. Mirgane , Dinanath D Patil, Vitthal S.Shivankar (International Journal of Advanced Science and Technology, 2020)
New and fast, effective and environment friendly pathway is presented herewith for the synthesis of nitrogen contacting heterocycles such as quinoxalines, benzimidazoles, benzothiazoles using Red Mud a efficient catalyst in acetonitrile as solvent at room temperature.